THE USE OF RELATIONSHIP MARKETING IN PEER-TO-PEER SHARING ACCOMMODATION - Pinto Sarmento, Mariana (2020)
The concept of sharing economy has grown in the last decade. In the tourism sector, platforms as Uber or Airbnb have gained an increasing dimension. While relationship marketing is an important topic of tourism management, the way it is used in peer-to-peer accommodations is a relevant re-search question, since it is a service based on the interaction between hosts and guests in order to generate trust when making the reservation, satisfaction during the stay, later, loyalty, positive feed-back on the platform, and long-term relationships. The purpose of this study is also to understand how relationship marketing can influence the business. Airbnb was selected as unit of analysis, since it is the platform with the highest growth and the great-est bet on interaction between users. As a qualitative research, 30 semi-structured interviews were conducted with hosts, in order to obtain their perspective on the importance that relationship market-ing can have in the business and how it is applied. Hosts with entire houses and hosts with rooms were interviewed, both from a B2C and a C2C business perspective. Cultural differences was also taken into account in this study. The results obtained show that the hosts are aware of the importance of interactions and personal contact with guests. The hosts also showed that they are concerned with personalising the service provided in order to increase the level of guest satisfaction. Different results were also identified depending on the type of business, type of accommodation or the culture and nationality of the stake-holders. The results have theoretical implications as they represent advances in the field of research on rela-tionship marketing in the tourism sector and peer-to-peer accommodation. This study is also im-portant for management, allowing hosts to understand the importance of relationship marketing, as well as several ways to apply it in their business.